2013
DOI: 10.1371/journal.pone.0063256
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Bone Substitute Engineered with Amniotic Epithelial Cells Enhances Bone Regeneration after Maxillary Sinus Augmentation

Abstract: BackgroundEvidence has been provided that a cell-based therapy combined with the use of bioactive materials may significantly improve bone regeneration prior to dental implant, although the identification of an ideal source of progenitor/stem cells remains to be determined.AimIn the present research, the bone regenerative property of an emerging source of progenitor cells, the amniotic epithelial cells (AEC), loaded on a calcium-phosphate synthetic bone substitute, made by direct rapid prototyping (rPT) techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(86 citation statements)
references
References 84 publications
3
81
1
1
Order By: Relevance
“…In fact, while osteogenic cell evolution appeared to be easily obtained by incubating oAECs isolated from mid [3, 21] to term gestation amnia, oAECs collected from early gestation amnia have proved to be highly refractory to the osteogenic-inductive cultural condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, while osteogenic cell evolution appeared to be easily obtained by incubating oAECs isolated from mid [3, 21] to term gestation amnia, oAECs collected from early gestation amnia have proved to be highly refractory to the osteogenic-inductive cultural condition.…”
Section: Discussionmentioning
confidence: 99%
“…The differentiation was assessed by Oil Red O and RT-PCR for a previously identified [21] adipogenic-specific marker, the lipoprotein lipase ( LPL ).…”
Section: Methodsmentioning
confidence: 99%
“…For example, Barboni et al (2013) demonstrated the osteogenic potential of ovine amniotic epithelial cells (oAEC) seeded on a CaP scaffold fabricated by material extrusion of a paste-like aqueous ceramic slurry of HA/ β -TCP. 4 When implanted in sheep to augment maxillary sinus defects, oAEC-seeding of the 3D printed CaP scaffolds significantly increased bone ingrowth into the defect and accelerated angiogenesis when compared to scaffolds without cells.…”
Section: D Printing For Bone Regenerationmentioning
confidence: 98%
“…A wide variety of cells have been used for such characterization, including osteoblasts, 7,14,20,24,71,91 preosteoblastic cells, 19,49 stromal cells, 22,71,98 osteoclasts, 21 mesenchymal stem cells (MSCs), 68,72 epithelial cells, 4 and Schwan cells. 80 Cell viability, 14,21,22,24,71,80,98 proliferation, 14,19,21,22,24,32,40,68,71,72,80,91 and cytotoxicity 19,91 assays all show a general consensus of favorable biocompatibility regardless of the 3D printing method using different biomaterials.…”
Section: D Printing For Bone Regenerationmentioning
confidence: 99%
“…Other therapeutic applications of AECs in laboratory animals include support of the regenerative process in tendon defects (Barboni et al, 2012a,b) via collagen type I production (Muttini et al, 2013), improvement in bone regeneration in vivo through implantation of scaffold-loaded AECs (Barboni et al, 2013), and reduction in the early host immune response to the scaffold (Jiawen et al, 2014). …”
Section: Aecs Transplantation To Improve Organ Functionsmentioning
confidence: 99%